ABOUT THE SCIENTIFIC SCHOOL OF ACADEMICIAN ABYLABEK ASANKANOV (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the activities of the scientific school of Abylabek Asankanov in Kyrgyzstan. Ethnic sociology and diasporology as a new scientific direction of ethnographic science are successfully developing in the system of ethnological science. A whole galaxy of ethnologists has grown up studying the traditional culture of the Kyrgyz people. Over forty years (from 1984 to 2024), the ethnological science of Kyrgyzstan, as an independent direction, has stepped forward significantly. The qualitative composition of researchers has changed.
Keywords: ethnology of Kyrgyzstan, scientific school, Abylabek Asankanov, ethnosociology, dias porology, traditional ethnology